1992
DOI: 10.1128/iai.60.10.4410-4413.1992
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Mycobacterium avium isolates to grow well or poorly in murine macrophages resides in their ability to induce secretion of tumor necrosis factor

Abstract: The results of this study show that clinical isolates ofMycobacterium avium fail into two categories in terms of their capacity to grow within murine bone marrow-derived macrophage cultures: those that grow progressively and those that are incapable of growing within such cells. Members of the first category were invariably of the smooth-transparent colonial type, while most of the second were of the smooth-domed type. In addition, this paper shows that although all isolates induced tumor necrosis factor (TNF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 17 publications
2
43
1
Order By: Relevance
“…before the onset of an immune response to the infectious organism) by the avirulent SmOp variant, namely TNF-Q. However, in vitro, neither the avirulent variant nor the more virulent SmTr variants triggered TNF-Q secretion, thus conflicting with the data obtained previously using an ELISA technique to detect secreted cytokine [16]. It was still possible that TNF was being produced and acted in an autocrine loop on the infected macrophages.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…before the onset of an immune response to the infectious organism) by the avirulent SmOp variant, namely TNF-Q. However, in vitro, neither the avirulent variant nor the more virulent SmTr variants triggered TNF-Q secretion, thus conflicting with the data obtained previously using an ELISA technique to detect secreted cytokine [16]. It was still possible that TNF was being produced and acted in an autocrine loop on the infected macrophages.…”
Section: Discussionmentioning
confidence: 64%
“…avium (A. Sarmento and R. Appelberg, manuscript in preparation). Thus, the hypothesis raised elsewhere [16], relating avirulence to enhanced TNF triggering, still applies to some situations of Myco. avium infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this context, differences in the LAM structure have been associated with the ability of the whole organism to survive within macrophages and to generate a productive infection. Further results obtained in an in vitro model of murine macrophage infection by M. avium isolates differing in their ability to grow intracellularly (virulence) suggest that a critical role in host resistance is played by the early phase of TNF-a response [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the interaction of M. avium isolates from AIDS patients and in vitro-cultured macrophages have shown that strains from patients with active disseminated disease appear to be more virulent and able to survive longer and multiply more rapidly in human monocyte cultures than strains isolated from environmental sources [1,6]. The ability of these M. avium strains to survive correlates strongly with their ability to delay the production of TNF-K [6]. This cytokine may be important in host defenses against mycobacterial pathogens [5,14].…”
Section: Introductionmentioning
confidence: 99%